Analysis of the use of ChatGPT in Question and Answer Systems as an Educational Tool - Ivan Felix; Syaeful Anas Aklani (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
In the digital era, the integration of artificial intelligence technologies like ChatGPT in education is becoming increasingly significant. This study seeks to investigate how ChatGPT can be utilized in school learning environments and assess its effectiveness in supporting both students and teachers. The research employs a desk study approach, analyzing various literature on the application of ChatGPT as a learning tool. The analysis aims to highlight the ways in which ChatGPT can assist teachers in areas such as content development, assessment, and classroom management. Additionally, the study will explore the benefits for students, including enhanced motivation, engagement, and problem-solving skills. Ultimately, the findings are expected to offer insights into the potential of ChatGPT to foster a more dynamic and adaptive learning environment while identifying challenges associated with its implementation. This research aims to provide actionable recommendations for educators and policymakers to effectively and ethically leverage this technology to enhance the quality of education.